(3OaY eVGQ GdGZPjIs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bGd eMeO Hf RcQjG GdQGRi QCjJ Cf Chda cJGHkG ai QaY eVGQ GdGZPjI s
(3BNQgG (B:s
(3bO fbUJ ChHWdJ hjTQH GdTQGH GdQjMGfi HGbOGM Ke QCjJ Cf gPG GdcJGH bO HdZ ef GdWhd ebOGQkG UGdMkG hCf gfG GdaUd eY Whdg NGQL Yf ZQV gPG GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(316) s
Keywords: (3GdWHs